Biological effects of short-term, high-concentration exposure to methyl isocyanate. IV. Influence on the oxygen-binding properties of guinea pig blood. - Maginniss, L A (1987)
Whole blood oxygen equilibrium curves (O2 ECs), blood buffer lines, and several hematologic properties were determined for adult guinea pigs exposed to 700 ppm methyl isocyanate (MIC) for 15 min. MIC inhalation effected a significant reduction of blood O2 affinity; the half-saturation pressure (P50) at 38 degrees C increased from the control (untreated) level of 22.8 +/- 0.1 mm Hg to values ranging from 28.5 to 43.7 mm Hg for experimental animals. MIC exposure had no apparent influence on O2 EC shape or CO2 Bohr effect. Erythrocyte volume, [metHb], O2 binding capacity, and combined red cell organic phosphate concentration (DPG + ATP) were not affected by MIC treatment. However, experimental animals experienced a severe metabolic acid-base disturbance; blood lactate concentration ranged from 8.6 to 24.0 mmole/L. Results indicate that lactic acidosis was solely responsible for increased blood P50 of MIC-treated animals. No direct effects of MIC on hemoglobin function were observed. Reduced Hb-O2 affinity, in conjunction with severe hypoxemia, compromised the guinea pigs' capacity for pulmonary O2 loading; at PaO2 of 30 mm Hg, Hb-O2 saturation (S) decreased from 66% S for controls to 42% S for MIC-treated animals.